EFFECT OF NIPPING ON GROWTH AND YIELD OF CHICKPEA - M. S. Baloch; M. Zubair (Journal of Animal and Plant Sciences, 2010)
Chickpea is an important crop in the cropping pattern supplying cheap protein diet especially for poor people. Over the years, however, low yields are more prominent declining acceptability of this crop. Apart from other production enhancement indicators, nipping appeared to be a factor increasing yield and yield contributing parameters. To investigate the appropriate nipping technique as well as to sort out combination of spacing and nipping, an experiment was conducted during 2008-09 with chickpea variety NIFA-2005. Nipping was done on four different crop growth stages viz. nibbling (topping), harvesting at 4" level, harvesting at ground level and control (no nipping) with rows 40 and 50 cm apart. Among the parameters studied, number of plants/plot, plant height and grain yield appeared statistically significant across nipping methods and row spacing whereas number of pods/plant, number of grains/pod and 1000-grain weight were found non-significant. Control plot produced tallest plants (78.80 cm) whereas maximum yield (1792 kg/ha) was obtained in nipping at ground level with rows 40 cm apart. The research concluded that nipping is a profitable practice for chickpea growers.
Keywords: Chickpea; nipping; spacing; growth; yield.